Implementing a Paperless Lecture Learning Strategy at Tulungagung University to Support the SDGs in the Era of Society 5.0 - Isro'iyah, Latifatul; Gesah Mukti Prabowo, Rachmad; Atikoh, Nurul; Roysul Rohim, Achmad (International Journal of Social Science, Education, Communication and Economics, 2024)
Technological advances have changed the learning landscape in higher education. Traditional lecture methods using paper are starting to be abandoned and replaced by technology-based solutions that are more efficient and environmentally friendly. The challenges of the Society 5.0 era related to digital skills, low literacy in Indonesia, and high levels of deforestation every year are serious problems and require support from various parties. This research explores paperless lecture strategies in supporting the Sustainable Development Goals (SDGs) in the era of Society 5.0 at Tulungagung University. The research method is through a descriptive-qualitative approach. This research shows that implementing paperless lectures can efficiently reduce environmental impacts. In Society 5.0, digital technology is used to improve the learning process to be more interactive and innovative. This research also analyzes the challenges and opportunities faced in adopting this learning method and its impact on the quality of education and achievement of the SDGs. This research also shows that paperless lectures positively impact environmental conservation and cost efficiency and improve the quality of learning.